Headache Secondary to Isolated Sphenoid Sinus Fungus Ball: Retrospective Analysis of 6 Cases First Diagnosed in the Neurology Department - Gao, Xiaoyu; Li, Bing; Ba, Maowen; Yao, Weidong; Sun, Chunjuan; Sun, Xuwen (Frontiers in Neurology, 2018)
Abstract Fungal sphenoid sinusitis is easily misdiagnosed in clinic, particularly for patients with normal immunological status. Due to the anatomic characteristics of sphenoid sinus, patients presented with various nonspeciﬁc symptoms and complications. Headache is the most common presentation, but location of headache is not fixed. We intended to analyze 6 cases of headache secondary to the isolated sphenoid sinus fungus ball (SSFB) which were first diagnosed in the Neurology Department. There was significant female predominance with mean ages of 55 years. They had repeatedly headache history from months to years. The headache was unilateral and usually on the side of lesions. Medication of pain relievers worked well in the beginning of SSFB, but not in the late stage of disease. Notably, all patients did not present positive nervous systemic signs. A preoperative computed tomography (CT) scan or magnetic resonance imaging (MRI) demonstrated the inflammation in sphenoid sinus. Some cases showed calcification in soft tissue or bone lesions of sinus wall. All of 6 patients undertook transnasal endoscopic sphenoidotomy without antifungal therapy after operation. Characteristic fungus ball (FB) was detected after histopathological examination. No headache recurrence was found after average 15.5 months follow-up. Our results suggested that transnasal endoscopic sphenoidotomy is the treatment of choice to remove the FB in sphenoid sinus with a low rate of morbidity and recurrence.